Tailing trouble - Scott, Laura, 1961- (Scott, Laura, 1961- Furry friends mystery, 2022)
"Thirty-something veterinarian Ally Winter has found a new "leash" on life since she moved back to her hometown of Willow Bluff, Wisconsin. But when she takes Domino, the black standard poodle she's boarding for the weekend, for a sunny September stroll along the shore of Lake Michigan, the diminutive dog dashes off, only to return with a single, polka-dotted, high-heeled shoe. Retracing Domino's paw prints back to a weeping willow tree, they find the other shoe. It's still on the foot of 20-year-old Pricilla Green--lying dead beneath the willow, with a silk scarf knotted tightly around her neck. Willow Bluff's finest--and handsomest--detective, Noah Jorgenson, is soon on the tail of the killer. But he has another worry on his mind when Ally's grandfather, a lifelong true-crime buff, starts to suspect that the recent burglary of a local big-box store may have some connection to Pricilla's murder. Noah cautions Ally to keep Gramps well away from the homicide investigation, but the old dog is drawn to danger like a puppy is to a squeaky ball." --